Design of LCL-filters for grid-connected voltage source inverters - Jayalath, Sampath (Department of Electrical Engineering, 2016)
LCL-filters are preferred over conventional L-filters for grid-connected voltage source inverters (VSI) due to their superior harmonic attenuation, smaller filter size and weight. The LCL-filter design process is complex and takes an iterative approach due to the coherence between the filter parameters and design requirements. The main aim of this thesis is to analyse different design variables that contribute to an efficient LCL-filter. The study carried out, falls under two sections. The first study was to understand the importance of ratio between the grid-side and inverter-side inductors, resonance frequency, reactive power production and attenuation of higher order harmonics in an LCL-filter. Based on the analysis, this thesis proposes a generalised LCL-filter design algorithm which avoids uncertainty in determining resonance frequency as the exact position of the resonance frequency is determined based on the design requirements. The proposed design method considers the LCL-filter as a single filtering unit rather than individual filtering contributions from passive components. The second study is extended to understand the limits of passive components based on the reactive power production limits (based on control structure), IEEE-519 harmonic limitations and the allowable switching losses or voltage drop across the entire filter. Based on the analysis, the thesis proposes an optimum operating point for an LCL-filter where the minimum inductance is realised to meet IEEE-519 harmonic current limitations for a given reactive power production while ensuring reasonable switching losses. Simulations and experimental results are presented to demonstrate the efficacy of the proposed two methods in terms of total harmonic distortion, harmonic attenuation and reactive power compensated.[Please note: This thesis file has been deferred until December 2016]